2021
DOI: 10.2174/1871523021666211222125403
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of the Pyridine-hexacyclic-steroid Derivative on a Heart Failure Model

Abstract: Background: Several drugs with inotropic activity have been synthesized; however, there is very little information on biological activity exerted by steroid derivatives in the cardiovascular system. Objective: The aim of this research was to prepare a steroid-pyridine derivative to evaluate the effect it exerts on left ventricular pressure and characterize its molecular interaction. Methods: The first stage was carried out through the synthesis of a steroid-pyridine derivative using some chemical strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…These data suggest that pyridine derivatives (6, 9 and 13) could interact with some biological molecules to produce changes in the cardiovascular system translated as changes in the perfusion pressure. Analyzing the hypothesis above mentioned and other reports which indicate that some pyridine derivatives produce changes in the perfusion pressure [13,14] through M2 muscarinic receptor activation. [15,16,[41][42][43] For this reason, in this research a theoretical evaluation on interaction of compounds 6, 9 and 13 with M2 muscarinic receptor was determinate.…”
Section: Biological Activitymentioning
confidence: 83%
See 2 more Smart Citations
“…These data suggest that pyridine derivatives (6, 9 and 13) could interact with some biological molecules to produce changes in the cardiovascular system translated as changes in the perfusion pressure. Analyzing the hypothesis above mentioned and other reports which indicate that some pyridine derivatives produce changes in the perfusion pressure [13,14] through M2 muscarinic receptor activation. [15,16,[41][42][43] For this reason, in this research a theoretical evaluation on interaction of compounds 6, 9 and 13 with M2 muscarinic receptor was determinate.…”
Section: Biological Activitymentioning
confidence: 83%
“…It is important to mention that the dose used in this research was based on previously reported studies which indicate that some compounds can produce effects on cardiovascular system at a dose of 001 nM. [13,27]…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing these data and other reports which suggests that some dibenzo derivatives can exert changes in intracellular calcium levels 45 46 . Besides, it is important to mention that in the literature there are some studies indicating that nifedipine can block the positive inotropic activity of some compounds 47 48 49 ; for this reason in this study the biological activity produced by Dibenzo[b,e]thiophene-11(6H)-one on left ventricular pressure was evaluated en the absence or presence of nifedipine drug ( type-L calcium antagonist) 50 . The results showed that Dibenzo[b,e]thiophene-11(6H)-one increases left ventricular pressure in a dose-dependent manner and this effect was inhibited in the presence of nifedipine.…”
Section: Discussionmentioning
confidence: 99%